MULTI FACTOR EXPLANATION TO IPO LONG RUN UNDERPERFORMANCE ANOMALY: SRI LANKAN EVIDENCE - Ediriwickrama, T.C; Azeez, A.A (Accounting Department,, 2015)
This paper focuses on IPO long run underperformance anomaly and the application of calendar time techniques to dissect anomalous behavior of IPO stocks. More specifically this paper will provide fresh evidence on how multi factor models work on a specific type of security (IPO stocks in this scenario) in an emerging market like Sri Lanka. It is analyzed IPOs over a period from 2000 to 2012 on Colombo Stock Exchange (CSE). Main finding of the study is that traditional market beta still remains strong despite the employment of latest multi factor models.Keywords: CSE, Initial public offerings, long run underperformance, Sri Lanka